Influence of franchisee characteristics on their commitment and the mediating role of trust - Mohd, Zalena (2022)
Franchising is one of the fastest channels for creating and developing entrepreneurs and promoting business growth in Malaysia. It is vital for the franchisor and his franchisees to have a long-term relationship. Despite the progress in franchising industry, there are challenges faced by the franchisees leading to the failure of various franchise business in Malaysia. Research shows that franchisees have not really optimised the franchise business opportunity as there are still only a handful of them in this business that are doing well. Trust and commitment are the two important variables for a good relationship in the franchising business. Hence this study investigates whether franchisee characteristics influence the franchisee’s commitment and the mediating role of trust. This study aims to better understand the impact of trust between the characteristics of franchisees and franchisees’ commitment. Moreover, the trust between the characteristics of franchisees and franchisees’ commitment to franchise organizations in Malaysia is under-explored. Over the years the characteristics evolved, there is still a need to identify the right characteristics that best fit the franchise business to mitigate the failure of existing franchise business. Understanding the influence of franchisee characteristics (entrepreneurial capacity, professional experience and financial capacity) on franchisee’s commitment provides additional insights into the literature in the area of franchise business. It also examines the mediating role of trust in the franchise business. Resource-based theory was used as a theoretical foundation in this study, which explicitly articulate that those resources need to be valuable, rare, difficult to imitate, and non-substitutable for the long-term success of any franchising business. Similarly, commitment-trust theory has also been used in this study as it emphasises that greater trust has a substantial impact on higher commitment from partners, which eventually improves business performance dramatically over time. Using a mixed methodology, questionnaires were distributed to 300 home-grown franchisees and six individual franchisees were interviewed. Using Partial Least Square Structural Equation Modelling, 258 usable responses were used for the analysis. The results provided an empirical evidence of the significant effect of entrepreneurial capacity and financial capacity support on the franchisee’s commitment. This study found that the results of professional experience effects were insignificant. This study revealed that trust is a significant mediator in the relationship between entrepreneurial capacity and financial capacity, hence supporting the theoretical premises. The study concluded that franchisee characteristics (entrepreneurial capacity and financial capacity) were found to be highly and critically important in meeting the needs of franchisee trust and commitment. The result also could be adopted by franchisors in determining the commitment amongst the franchisees that can become the best candidate for the franchise business.